PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBASIS BUDAYA LOKAL TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Jannah, Sri Rodiyatul; Sunaengsih, Cucun; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
Mathematical critical thinking ability is way to think logically and reflectively which is important to develop, until student can solve the matter in their daily life. Efforts to gain mathematical critical thinking is through RME approach on the basis of local culture. This research is quasi experimental, nonequivalent control group design. The Population is fifth grade of Elementary School in Kertasemaya region which include into medium group. This research uses cluster sampling. SDN Tulungagung III is experimental class and SDN Kliwed 1 as control class. The result found that RME approach on the basis of local culture influence to increase students’ mathematical critical thinking significantly. RME approach on the basis of local culture has positive influence to increase student mathematical critical thinking ability better than conventional approach significantly. Many of students is giving positive respond towards RME approach on the basis of local culture in the group learning, the use of media, and LKS that is used in the learning process.